MENGIKIS PERILAKU KORUPSI PADA BIROKRASI PEMERINTAHAN - irfan setiawan (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2016)
AbstractCorruption is a problem it should be a concern to everyone. One of the causes that is the low morale as well as ofﬁ cials and public awareness about corruption itself. Minimize the movement habitsand corruption are other alternatives that should be pursued by the government. Space is narrowedin the implementation of government services, so the opportunity to behave corruption can be eroded.Some things you can minimize the space for corruption is anti-corruption education, standard operatingprocedures services, e-services and increase community participation.